Pengaruh Transtibial Prosthesis terhadap Activity Of Daily Living Pasien Amputasi Bawah Lutut - Muhammad Syafii; Nur Rachmat (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: The physical condition of patients with transtibial amputations affects the fulfillment of activity of daily living. Transtibial Prosthesis is used to increase the patient's activity abilities. This research is to find the effect of using transtibial prostheses on the activity of daily living. This study aims to determine the effect of the use of transtibial prostheses on the activities of daily life. Methods: This research method uses Quasi Experiment in the form of two-group post test only design. The study population was transtbial amputee at PT. Kuspito Prosthetic Orthotics. The sample in this study 40 people, namely 20 people using Transtibial Prosthesis, 20 people using Axial Crutches. The study was conducted at PT. Kuspito Prosthetic Orthotics from April to May 2019. This study used an observation sheet prepared by Kempen, et al (1996), namely The Groningen Activity Restriction Scale. Results: The normality test used is Shapiro Wilk. Mann Whitney test resuls shows an average difference of ADL between users of transtibial prosthesis users (22.40) and axillary crutch users (19.95) with a p value = 0.008 where a p value <0.05. Conclusion: So there is a difference in ADL which is statistically significant in patients using transtibial prosthesis and patients using axillary crutches. Where for transtibial prosthesis users better in ADL than axillary crutch users.